Laboratory Diagnostics in Thrombophilia - Linnemann, Birgit; Hart, Christina (Hämostaseologie, 2019)
A thrombophilic disorder is a hereditary or acquired condition that increases the risk of thrombosis. The most common hereditary thrombophilias that predispose to venous thrombosis in the Caucasian population are the heterozygous forms of the factor V Leiden and prothrombin G20210A mutation that are generally detected by direct DNA genotyping. Immunologic antigen assays and chromogenic or clot-based activity assays are used to identify deficiencies in the natural coagulation inhibitors antithrombin, protein C and protein S. Because pre-analytical errors and acquired causes of low antithrombin, protein C or protein S levels are considerably more common than hereditary deficiencies, all potential conditions that may lower activity levels of the natural coagulation inhibitors (e.g. concomitant liver disease, pregnancy, anticoagulant therapy) must be considered and excluded before the diagnosis of an inhibitor deficiency can be made. To avoid misclassification, the diagnosis should not be made based on a single abnormal test result. Thus, repetitive testing when the patient is not on anticoagulant therapy is mandatory to confirm the diagnosis. Screening for antiphospholipid syndrome (APS) comprises testing for lupus anticoagulants (LAs) and the presence of IgG or IgM antibodies directed against phospholipids and phospholipid-binding proteins such as β-2-glycoprotein-I. A combination of clot-based assays has been recommended to demonstrate LA activity, whereas solid-phase immunoassays allow the detection of anti-cardiolipin and anti-β-2-glycoprotein-I antibodies. The diagnosis of APS requires the persistence of antiphospholipid antibodies for at least 12 weeks together with thrombotic and/or obstetric features of APS.
Keywords: thrombophilia; factor V Leiden mutation; prothrombin; natural coagulation inhibitor; antiphospholipid antibodies